MEMBONGKAR PILIHAN GEN Z: Bagaimana Kualitas, Kesadaran Kesehatan, dan Harga Menentukan Kepuasan Pada Makanan Tradisional - Christiawan, Daniel Grace; Yuliana, Rahmi; Terasa, Irya Nan (JURNAL CAPITAL : Kebijakan Ekonomi, Manajemen dan Akuntansi, 2025)
This study aims to analyze the influence of product quality, health consciousness, and price on purchase satisfaction among Generation Z consumers of traditional foods in Semarang City. The increasing health awareness after the Covid-19 pandemic and shifts in consumption patterns serve as the foundation for this research. A total of 100 respondents were selected using purposive sampling, and data were collected through an online questionnaire. The data were analyzed using multiple linear regression with SPSS. The results of the regression analysis show that the research model is feasible, as evidenced by the simultaneous test (F-test) which obtained F-value = 52.914 > F-table = 2.70 with a significance level of < 0.001, indicating that all independent variables jointly influence purchase satisfaction. The model also has strong explanatory power, with an Adjusted R² value of 0.611, meaning that 61.1% of the variation in purchase satisfaction is explained by product quality, health consciousness, and price. Partially, product quality does not significantly influence purchase satisfaction. This is indicated by a t-value = 0.940 < t-table = 1.98498 and a significance value of 0.349 > 0.05, leading to the rejection of H1. In contrast, health consciousness shows the strongest effect with a t-value = 6.807 > 1.98498 and a significance level < 0.001, demonstrating that health awareness plays a crucial role in shaping satisfaction toward traditional foods in the post-pandemic era. The price variable also significantly influences purchase satisfaction, supported by a t-value = 3.609 > 1.98498 and significance < 0.001, thus accepting H3. The regression coefficients further indicate the magnitude of influence for each variable—product quality (β = 0.046), health consciousness (β = 0.490), and price (β = 0.197). These findings confirm that health awareness and competitive price perception are the dominant factors driving purchase satisfaction among Gen Z consumers of traditional foods in Semarang City.